A new combination in Verbenaceae and a new synonym in Lamiaceae from Brazil - Salimena, Fátima Regina G.; Múlgura, Maria Ema; Harley, Raymond (Phytotaxa, 2012)
A new combination is provided for a species of Verbenaceae from Brazil, Lippia horridula comb. nov., which was originally described as Eriope horridula (Lamiaceae). Lippia adpressa is here recognized as a synonym of Hyptis obtecta (Lamiaceae).